Pendampingan Tahfiz Al-Qur'an untuk Membangun Karakter Siswa di R.A Qur'an Al-Ghozali Desa Sukorejo Ponorogo - Ullul Ega Nur Ariani; Ibnu Muchlis; Medina Nur Asyifa Purnama (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Tahfiz Quran assistance at the RA Qurán Al Ghozali institution, which, as an Islamic-based kindergarten, strives to instill Islamic character in real life to students. In this effort, the school holds a Tahfiz Extracurricular program; through this activity, the school has a strategy and has the goal of forming an Islamic character in this sophisticated era. The school is optimistic about the activities that have been running for several years to improve and strive for the formation of students' Islamic character. The assistance of Tahfiz Qur'an in building the character of students in RA Qur'an Al Ghozali Sukorejo Village using the Asset-based community development (ABCD) method is considered the right approach to the above problems. This is because ABCD is an approach in community development that is in a large stream of seeking the realization of a social life order where the community is the actor and determinant of development efforts in their environment or what is often called Community-Driven Development (CDD). Community development efforts must be carried out from the beginning by placing humans in a position to know what strengths they have and all the potential assets they have that have the potential to be utilized. Only by knowing the strengths and assets will it be hoped that humans will know and be excited to be involved as actors and, therefore, have the initiative in all efforts to improve. By knowing the strengths and assets owned and having a change agenda that is formulated together, the sustainability of a program to improve the quality of life is expected to be realized. Through the ABCD approach, community members are facilitated to formulate an agenda for change that they consider important. The habituation of the Tahfiz Qur'an in RA Qur'an Al Ghozali Sukorejo Village can foster discipline, increase devotion to children, control emotions, and improve children's cognitive development. The Qur'an tahfiz program can foster good character and prepare children to become a generation that is in accordance with the sunnah and the Qur'an.